Impact of Varied Ag-GO Ratios on the Electrochemical Enhancement of Vitamin D Detection - Kiki C.; Mohd Said N.A.; Mohammad Haniff M.A.S.; Zaid M.H.M.; Mohd Nashruddin S.N.A.; Wee M.F.M.R.; Menon P.S. (Institute of Electrical and Electronics Engineers Inc., 2025)
Rapid detection of vitamin D levels in human serum presents significant benefits for diagnosing deficiency and managing treatments. This work reports the preparation and application of silver-graphene oxide (Ag-GO) composites for the development of vitamin D biosensors through chemical reduction method of silver nanoparticles (AgNPs) in aqueous suspension of graphene oxide (GO). Different concentrations of graphene oxide (GO) and silver (Ag) were tested to identify optimal electrochemical enhancements of screen-printed carbon electrodes (SPCE). By synthesizing Ag-GO composites and modifying SPCE, the electrochemical behaviour was investigated using differential pulse voltammetry (DPV). The Ag-GO composite prepared were characterised using Fourier-Transform infrared spectroscopy (FTIR) and field-emission scanning electron microscopy (FESEM). AgGO synthesised from 2?10-3 mol dm-3 AgNO3 and 1.0 g/L GO provided the most favourable conducting environment for electron transfer from the electrolyte to the electrode. The modified SPCE exhibited more than a threefold enhancement in peak current, reaching 37.98 ?A, compared to an unmodified electrode. ? 2024 IEEE.